A paradigm for applying risk and hazard concepts in proactive planning: application to rainfed agriculture in Greece [Part 2. Examples of application] - Tsakiris G. (Drought management guidelines technical annex, 2007)
The concepts of risk and hazard have been used with different meaning in a wide spectrum of disciplines. Even in the area of natural hazards such as the floods and droughts the definitions used for all the related terms are still confusing the scientific community and the stakeholders. The objective of this chapter is to attempt to clarify some of these terms and propose a methodology for risk assessment. Emphasis is given to the estimation of risk of the affected areas due to the occurrence droughts and the proposed methodology. Simplified examples are presented for illustrating the use of these terms. Particular attention is given to the concept of vulnerability mainly in relation to proactive planning.